EXPERIMENTAL INVESTIGATION AND COMPARATIVE ANALYSIS OF NANO-SILICA INCORPORATION ON STRENGTH PROPERTIES OF CONCRETE - B. Sandeep; Dr.G.V. V.Satyanarayana (Utilitas Mathematica, 2025)
Emissions from cars, industrial operations, and urbanization are only a few of the many causes of the disturbing rise in environmental pollution. Because of this, the concrete's resistance is reduced.Here we look at how M70 grade concrete performing when partially substituted with Silica Fume, Fly Ash, and Nano Silica in the cement mix. Because of its microscopic particle size, nano-silica shows promise as a concrete addition that might improve the material's density and performance. Prior studies found that tensile characteristics improved by 10% and workability decreased by 5% when 10%, 15%, and 3% of the total cement was replaced with Silica Fume, Fly Ash, and Nano Silica, respectively, in M50 concrete. The mechanical characteristics and workability of M70 Grade concrete are examined in this study. Subsequently, 11% fly ash, 10% silica fume, and 0-4% nano-silica in 1% increments replace cement in the mixture, which is then made and evaluated. The findings show that 10% silica fume, 11% fly ash, 3% nano silica, and cement make up the ideal composition for this application.